1999
DOI: 10.1046/j.1365-2826.1999.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive POMC‐Derived Peptides and Cytokines in the Chicken Thymus and Bursa of Fabricius Microenvironments: Age‐Related Changes

Abstract: Changes from hatching to the involutive stage in the thymus and bursa of Fabricius of Gallus domesticus were studied. Pro-opiomelanocortin (POMC)-derived peptides and cytokines were also tested by immunocytochemical procedures. Thymic histological modifications appeared at 3 months and involved an increase in connectival argyrophilic reticular fibres, a proliferation of non-epithelial cells in the reticulum network, the presence of mucous cells and small mucous cysts, and an increase in the number of eosinophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 34 publications
1
27
0
4
Order By: Relevance
“…In bone marrow and bursa, less is known about regulatory factors. The avian bursa contains immunoreactive ACTH (22), but CRH has not been reported. The bursa also contains bursal antisteroidogenic peptide (BASP), which suppresses adrenal glucocorticoid production in vitro (7).…”
Section: Regulationmentioning
confidence: 97%
“…In bone marrow and bursa, less is known about regulatory factors. The avian bursa contains immunoreactive ACTH (22), but CRH has not been reported. The bursa also contains bursal antisteroidogenic peptide (BASP), which suppresses adrenal glucocorticoid production in vitro (7).…”
Section: Regulationmentioning
confidence: 97%
“…As far as ACTH is concerned, proopiomelanocortinrelated molecules and cytokines occurred in thymic cells from 4-day-old chicken, and their number increased with age [52]. Gap junction-mediated cell coupling among thymic epithelial cells showed up-regulation after ACTH exposure [10].…”
Section: Discussionmentioning
confidence: 98%
“…The lymphoid tissue was substituted by fibrous tissue, and inside it there were cysts covered by cuboid epithelial cells filled with hyaline substance and leucocytes. Franchini and Ottaviani (1999) observed that in Gallus domesticus, the histological modifications in the bursa appeared at 2 months and that β-endorphin appeared in the FAE and in dendriticreticular cells between 4 days and 2 months, while ACTH, α-MSH and cytokine-like molecules appeared in follicles after 2 months.…”
Section: Plical Epitheliummentioning
confidence: 93%